Relationship between Arg753Gln Toll-like receptor 2 and Asp299Gly Toll-like receptor 4 genetic variations and susceptibility to colorectal cancer in southern Iran - Hosseini, Seyed Vahid; Mojtahedi, Zahra; Beizavi, Zahra; Khazraei, Hajar; Zamani, Mozhdeh (Archives of Biological Sciences, 2018)
Paper description: Comprehensive genetic studies in different populations contribute to a better understanding of the genetic mechanisms of diseases. Examination of genetic variations of regulators of immune and inflammatory responses, Arg753Gln TLR2 (rs5743708) and Asp299Gly TLR4 (rs4986790), evaluated for the first time in colorectal cancer patients and healthy controls in southern Iran, showed that Arg753Gln TLR2 but not Asp299Gly TLR4 can be considered as a risk factor for colorectal cancer incidence, especially in men. This result contributes towards a detailed assessment of the role of TLR genetic variations in colorectal cancer. Abstract: Variations in Toll-like receptor 2 (TLR2) and Toll-like receptor 4 (TLR4) encoding genes have been associated with tumorigenesis through the disruption of immune and inflammatory responses. The aims of this study were to evaluate the two single nucleotide polymorphisms (SNPs) of the genes Arg753Gln TLR2 (rs5743708) and Asp299Gly TLR4 (rs4986790) in colorectal cancer patients in southern Iran. Colorectal cancer patients and healthy controls were included in this study (150 Persian subjects in each group). Blood samples were used for genotyping by the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method. The association between these SNPs and colorectal cancer and clinicopathological factors, including age, gender, tumor stage and differentiation were also investigated. A significant association was found between Arg753Gln TLR2 SNP and colorectal cancer. This SNP was significantly more frequent in male patients. However, there was no association between Asp299Gly TLR4 and colorectal cancer. Therefore, Arg753Gln TLR2 SNP can be considered as a risk factor for colorectal cancer incidence in southern Iran, especially in men. Further investigations in other populations are recommended in order to assess the association of this SNP with colorectal cancer. https://doi.org/10.2298/ABS180812043H Received: August 12, 2018; Revised: September 18, 2018; Accepted: September 18, 2018; Published online: September 26, 2018 How to cite this article: Hosseini SV, Mojtahedi Z, Beizavi Z, Khazraei H, Zamani M. Relationship between Arg753Gln Toll-like receptor 2 and Asp299Gly Toll-like receptor 4 genetic variations and susceptibility to colorectal cancer in Southern Iran. Arch Biol Sci. 2018;70(4):775-9.